2018
DOI: 10.2147/cmar.s157837
|View full text |Cite
|
Sign up to set email alerts
|

Optimized multiparametric flow cytometric analysis of circulating endothelial cells and their subpopulations in peripheral blood of patients with solid tumors: a technical analysis

Abstract: BackgroundCirculating endothelial cells (CECs) and their subpopulations could be potential novel biomarkers for various malignancies. However, reliable enumerable methods are warranted to further improve their clinical utility. This study aimed to optimize a flow cytometric method (FCM) assay for CECs and subpopulations in peripheral blood for patients with solid cancers.Patients and methodsAn FCM assay was used to detect and identify CECs. A panel of 60 blood samples, including 44 metastatic cancer patients a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Endothelial cells can enter circulation as CECs when sloughing off vessel walls and as endothelial progenitor cells (EPCs) when mobilized from the bone marrow. 36 Both CECs and their populations, which can be enumerated by flow cytomery, 56 58 could potentially serve as biomarkers for the prognosis and prediction of various solid tumors. 36 CECs and EPCs appear to change dynamically during the course of chemotherapy of patients with breast cancer.…”
Section: Circulating Biomarkersmentioning
confidence: 99%
“…Endothelial cells can enter circulation as CECs when sloughing off vessel walls and as endothelial progenitor cells (EPCs) when mobilized from the bone marrow. 36 Both CECs and their populations, which can be enumerated by flow cytomery, 56 58 could potentially serve as biomarkers for the prognosis and prediction of various solid tumors. 36 CECs and EPCs appear to change dynamically during the course of chemotherapy of patients with breast cancer.…”
Section: Circulating Biomarkersmentioning
confidence: 99%
“…Van Craenenbroeck et al ( 2008 ) found moderate to poor agreement between six different flow cytometric gating strategies for EPC quantification. Finally, flow cytometry related analytical factors possibly can explain part of the variability on findings within the same clinical population since the volume of blood samples, storage protocol, anti-coagulant tube selection, a wash step or not for red blood cell lysis and units of EPC expression are essential for reliable and accurate EPC enumeration (Hoymans et al 2012 ; Van Craenenbroeck et al 2013 ; Zhou et al 2018 ).…”
Section: Discussionmentioning
confidence: 99%